2004
DOI: 10.1177/1043986204269381
|View full text |Cite
|
Sign up to set email alerts
|

Violent Encounters

Abstract: This study identifies key factors from the criminal events perspective that affect the lethality of violent encounters. Data for this research are derived from the National Incident-Based Reporting System of the FBI. Using logistic regression analysis, the effects of several contextual factors, including weapon, location, time of incident, circumstances, and victim and offender characteristics and relationships are explored. Analysis reveals that variables from each of the six categories affect the lethality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 31 publications
(42 reference statements)
2
6
0
Order By: Relevance
“…In addition, most GSW victims were young, with a mean age of just under 28 years, which is consistent with findings from other jurisdictions (Hipple et al, 2019). In contrast to age, race and ethnicity were not found to have a significant relationship with fatality among this sample of gunshot victims much like what was found in Weaver et al (2004). As was previously discussed, we found that when the age of the victim increases, the predicted probability of a fatality increases (Weaver et al, 2004) which suggests that young people are more likely to survive their wounds.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, most GSW victims were young, with a mean age of just under 28 years, which is consistent with findings from other jurisdictions (Hipple et al, 2019). In contrast to age, race and ethnicity were not found to have a significant relationship with fatality among this sample of gunshot victims much like what was found in Weaver et al (2004). As was previously discussed, we found that when the age of the victim increases, the predicted probability of a fatality increases (Weaver et al, 2004) which suggests that young people are more likely to survive their wounds.…”
Section: Discussionsupporting
confidence: 89%
“…GSW victims between 18 and 44 years old make up the largest proportion of all those injured, and 75% of all victims of gun violence are in economically disadvantaged neighborhoods (Avraham et al, 2018). Indeed, past research has consistently found a positive relationship between the age of the victim and GSW fatality (Libby & Wright, 2009;Weaver et al, 2004). More recently, however, limited access to medical care, including measures of proximity to trauma care, has garnered attention in the study of GSW victim mortality.…”
Section: The Role Of Geography In Gunshot Fatalitymentioning
confidence: 99%
“…Our goal was to identify factors associated with gun violence incidents involving multiple victims, rather than just those with multiple fatalities. Because the lethality of a violent encounter may be affected by contextual factors (e.g., Weaver et al, 2004), the shooter's intent may be more accurately reflected by the number of victims shot rather than the number killed. The lethality perspective recommends that homicide research focus on "potentially lethal criminal actions rather than on completed homicides…" (Harris, Thomas, Fisher, & Hirsch, 2002, p. 156).…”
Section: Our Studymentioning
confidence: 99%
“…For instance, Pino (2005) used CEP to conduct a qualitative case study on serial rape. Weaver et al (2004) examined how factors identified through the use of CEP (e.g., location, time, and victim characteristics) related to the lethality of violent encounters. Grommon and Rydberg (2014) used CEP in their interdisciplinary study of criminological and public health correlates of firearm injury severity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%